Knowledge, Prevention, and Handling Sexually Transmitted Diseases among Transvestite Commercial Sex Worker - Jasmen Manurung; Ivan Elisabeth Purba; Hana Ike Dameria Purba; Jek Amidos Pardede (LPPM STIKES KENDAL, 2021)
Laut Dendang Village has experienced the phenomenon of increasing the number of Transvestites who work as a commercial sex worker around Titi Laut Dendang. Preliminary surveys show an increase in sexually transmitted disease screening for transvestite in a clinic and indicate a high incidence of sexually transmitted disease among Transvestite-CSWs. This study uses phenomenological studies that aim to explore the causes of the high incidence of STI disease among Transvestite-CSWs in the open area of Percut Sei Tuan District. The informants in this study were three Transvestite-CSWs who sold themselves around the bridge of Laut Dendang and were triangulated on their sexual partners. Information was collected by in-depth interviews. The results showed that informants were only able to associate STIs with HIV/AIDS, didn’t know about STIs, and didn’t want to use condoms. The Transvestite-CSWs who is infected performs treatment by inserting toothpaste into the anus, taking antibiotics that are not according to the dosage used, and a few of them carried out HIV/AIDS and genital tested and counseling in the Community Health Movement (GSM). It causes the knowledge, prevention and management of sexually transmitted diseases to Transvestite-CSWs is still low.